Literature Study Of Restaurant Tax Collection With Online System Implementation - Cici Tri Jayanti; Yulia Novita Sari; Ella Juwitasari; Lukman Hakim; Krisna Putra; Nurcahyaning Dwi Kusumaningrum (Journal of International Multidisciplinary Research, 2023)
This study aims to determine the implementation of restaurant tax collection with an online system in several regions in Indonesia. This research uses the method of literature study. The literature study method is a method by collecting and reviewing some previous research and then drawing conclusions from the previous research. The results obtained from the study of several literature are obstacles and supporting factors of online system implementation in several regions are more or less the same and there are some differences. The influencing factor is the quantity of tools and human resources in each region. This can affect the income of these areas.